Bridging Cultures Through Modulation: A Cross-Cultural Analysis of Soekarno's 1955 Speech Translation - Parthama, I Gusti Ngurah; Setianingsih, Ni Ketut Alit Ida; Giri, Ni Luh Kade Yuliani (Indonesian literature Program, Faculty of Humanities, Diponegoro University, 2025)
Translation is a vital tool for bridging linguistic and cultural gaps. It also provides cross-cultural communication and understanding. This study explores the use of modulation as a translation technique in Soekarno’s 1955 Asian-African Conference speech. Modulation, defined as a shift in perspective or expression to suit the target language’s norms, is essential for maintaining the original text’s meaning. While, at the same time, it is also ensuring cultural and linguistic relevance. This research focuses on how modulation adapts rhetorical elements, idiomatic expressions, and cultural nuances in political text translation. The research employed a qualitative method to analyze bilingual data from the English and Indonesian versions of Soekarno’s speech. The data were collected through documentation and systematically categorized into compulsory and optional modulation types based on Vinay and Darbelnet’s framework. Examples were analyzed to understand how modulation preserves meaning and cultural resonance. The findings were presented descriptively to highlight the role of modulation in cross-cultural translation. The findings reveal that modulation effectively adapts linguistic structures and cultural concepts to the target language. Examples such as translating peoples into bangsa-bangsa and terrific into hebat demonstrate the translator’s ability to maintain rhetorical impact and cultural relevance. The study also underlines the significance of modulation in ensuring that translated texts in relevant with their audience while preserving the original message’s intent. This research contributes to the understanding of modulation as a strategic tool for achieving effective and meaningful translations in political and historical contexts.